Educating Students to Create Trustworthy Systems. - Swart, R.S (IEEE Security and privacy : building confidence in a networked world)
Computer science's long-standing tradition of computer security education has focused primarily on designing secure and reliable systems that can ensure information confidentiality, integrity, and availability. This tradition is geared toward preparing students for typical paradigms, such as writing secure code, providing authentication and access control, and developing policies to limit exposure to vulnerabilities and protect users' rights. Faculty and industry must find novel, cross-disciplinary approaches to educating security professionals to fully address this array of issues. In this article, we analyze barriers to effective security education and offer suggestions for improving cooperation among computer science, business management, information systems. and other technology departments.